Postpartum serum biochemical profile in Mehsana buffaloes during non-fertile and fertile oestrus - PATEL, K K; JACOB, NINAN; KAVANI, F S; VADODARIA, V P (The Indian Journal of Animal Sciences, 2013)
Eighteen normally calved Mehsana buffaloes studied for postpartum oestrus (non-fertile and fertile oestrus) revealed higher levels of serum total cholesterol (P